2014
DOI: 10.4028/www.scientific.net/kem.616.183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of A-Type Zeolite from Flat Glass Recycle by Hydrothermal Treatments and its Evaluation

Abstract: Synthesis of monolithic A-type zeolite (LTA) was attempted by hydrothermal processing from recycling flat glass. Crashed flat glass were pretreated and subsequently hydrothermally treated at 95°C for 24 h. As a result, monolithic A-type zeolite without another phase was successfully synthesized by the hydrothermal treatments. The synthetic condition was clarified during the pretreatment and hydrothermal treatments. The development of hydrothermal process for recycle of flat glass was carried out since the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The Cs + in solution after leaching for 24 h was not-detected by ICP. As a result, it was confirmed that there were no leaching from Cs + trapped zeolite/glass samples were in the water with pH 7 for 24 h. 21) From these results, it was found that hybrid zeolite/glass samples heated at 700°C had the ion exchange abilities of 20% against Sr 2+ and of 80% against Cs + . Furthermore, these hybrid zeolite/glass samples are thought to be useful for Sr 2+ and Cs …”
Section: Kamitani Et Al: Fabrication and Evaluation Of Hybrid Materisupporting
confidence: 64%
“…The Cs + in solution after leaching for 24 h was not-detected by ICP. As a result, it was confirmed that there were no leaching from Cs + trapped zeolite/glass samples were in the water with pH 7 for 24 h. 21) From these results, it was found that hybrid zeolite/glass samples heated at 700°C had the ion exchange abilities of 20% against Sr 2+ and of 80% against Cs + . Furthermore, these hybrid zeolite/glass samples are thought to be useful for Sr 2+ and Cs …”
Section: Kamitani Et Al: Fabrication and Evaluation Of Hybrid Materisupporting
confidence: 64%
“…To date, the authors have proposed several applications of the above porous glass as a carrier for ultrafine metal particles [9] or hydrate crystals [10,11]. Besides, there have been many works that applied hydrothermal treatment for glass recycling to fabricate advanced materials [12,13,14] and surface structure modification of glass materials [15,16,17].…”
Section: Introductionmentioning
confidence: 99%